The mediating role of corporate entrepreneurship for external environment effects on performance - Kearney, Claudine; Hisrich, Robert D.; Antoncic, Bostjan (Journal of Business Economics and Management, 2013)
A model is proposed that tests the antecedents and the mediating effect of corporate entrepreneurship on the external environment-performance relationship within private and public sector organizations. Hypotheses were tested using data from a sample of chief executive officers in 51 private sector organizations in the United States, 141 private sector organizations in Slovenia and 134 public sector state and semi-state enterprises in Ireland. Data was analyzed using hierarchical regression analysis. The results show that dynamism and munificence effects on performance are mediated by an organization's corporate entrepreneurship in the private sector and munificence effects on performance are mediated by an organization's renewal in the public sector and that renewal must be in place to maximize the effect of munificence on performance. The results support a model that incorporates an extensive and diverse literature into a single model and helps illuminate similarities and differences of corporate entrepreneurship between the private sector and the public sector. The study shows that an integrative model and the interplay among the constructs yields new insights unavailable to single and focused approaches. It offers new insights about corporate entrepreneurship, not only as a discrete pursuit, but also as a construct that shapes and extends organizational performance.